Controlling Dielectric and Magnetic Properties of PVdF/Magnetite Nanocomposite Fibre Webs - A. P. Venugopal; O. Cespedes; S. J. Russell (International Journal of Polymer Science)
The ability of filtration and separation media containing fibres to remove impurities from oil, water, and blood can be enhanced using magnetic fields. The ability to regulate the dielectric and magnetic behaviour of fibrous webs in terms of superparamagnetic or ferromagnetic properties by adjusting material composition is fundamental to meeting end-use requirements. Electrospun fibres were produced from PVdF (polyvinylidene fluoride) and nanomagnetite (Fe3O4 nanoparticles) from solutions of PVdF in dimethylacetamide containing Fe3O4 nanoparticle contents ranging from 3 to 10 wt%. Fibre dimensions, morphology, and nanoparticle agglomeration were characterised by environmental scanning electron microscopy (ESEM) and field emission gun transmission electron microscopy (FEGTEM). Dielectric behaviour of the fibre webs was influenced by web porosity and the Fe3O4 nanoparticle content. Impedance analysis of the webs indicated an increase in dielectric constant of ∼80% by the addition of 10 wt% Fe3O4 nanoparticles compared to 100 wt% PVdF. The dielectric constants of the webs were compared with those obtained from the theoretical mixing models of Maxwell and Lichtenecker. Vibrating sample magnetometer (VSM) magnetisation measurements indicated a blocking temperature above 300 K suggesting ferrimagnetic rather than superparamagnetic behaviour as a result of Fe3O4 nanoparticle agglomeration within fibres.